Oncological biomarkers - Ozben, Tomris (Henry Stewart Talks, 2026)
Tumor markers in the current and future clinical practice, Methods for tumor marker detection, International Standards (IS) & Reference Preparations (IRP), Combining tumor markers for improving diagnostic performance, Clinical uses of tumor markers, Genetic markers